MENINGKATAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI MODEL PEMBELAJARAN KOLABORASI - Roqoiyah, Tatik (Universitas Islam Darul Ulum, 2016)
This study was aimed to determine the increase of learning achievement of Islamic Education after the implementation of collaborative learning model at the fifth grade in The State Elementary School of Sukosongo, Kembangbahu â Lamongan in the academic year ofÂ 2015/2016. To obtain the necessary data, the data collected by observation and tests. The study was conducted during two cycles. Each stage of the cycle was done as planning, action, observation, reflection. The results of data analysis showed that the increase of studentsâ achievement with increased of learning achievement was enormous which the average learning achievement at the first cycle of 62.54 into 81.67 at the second cycle and classical mastery learning value from 33.33% to 91.67% , It could be concluded that there was an increase of learning achievement of Islamic education through collaborative learning at the fifth grade in The State Elementary School of Sukosongo, Kembangbahu â Lamongan in the academic year ofÂ 2015/2016.